Effect of Injection Timing on the Operation of Hydrogen-Fuelled Free- Piston Linear Generator Engine during Starting - Abdulwehab A., Ibrahim; Ezrann Zharif, Zainal Abidin; A. Rashid, A. Aziz; Saiful A., Zulkifli (Society of Automotive Engineers of Japan, Inc, 2013)
A linear engine type with piston assembly that swings between two oppositely placed combustion chambers considered in this study. The study investigated the effect of injection timing on starting of the engine. The injection position varied at five different positions (17mm to 27mm) before the maximum switching limit of the engine reached. It was observed that advancing the injection position in free-piston engine slows down the compression stroke and increases the combustion duration. Furthermore, lower peak pressure and rate of heat release occurred at 17 mm, 20 mm, and 23 mm injection timing. Relatively stable operation of the engine was achieved at 25 mm.